A VLP-based vaccine targeting domain III of the West Nile virus E protein protects from lethal infection in mice - Beck Markus; Keller Iris; Martina Byron EE; Jennings Gary T; Spohn Gunther; Pumpens Paul; Osterhaus Albert DME; Bachmann Martin F (Virology Journal, 2010)
Abstract Background Since its first appearance in the USA in 1999, West Nile virus (WNV) has spread in the Western hemisphere and continues to represent an important public health concern. In the absence of effective treatment, there is a medical need for the development of a safe and efficient vaccine. Live attenuated WNV vaccines have shown promise in preclinical and clinical studies but might carry inherent risks due to the possibility of reversion to more virulent forms. Subunit vaccines based on the large envelope (E) glycoprotein of WNV have therefore been explored as an alternative approach. Although these vaccines were shown to protect from disease in animal models, multiple injections and/or strong adjuvants were required to reach efficacy, underscoring the need for more immunogenic, yet safe DIII-based vaccines. Results We produced a conjugate vaccine against WNV consisting of recombinantly expressed domain III (DIII) of the E glycoprotein chemically cross-linked to virus-like particles derived from the recently discovered bacteriophage AP205. In contrast to isolated DIII protein, which required three administrations to induce detectable antibody titers in mice, high titers of DIII-specific antibodies were induced after a single injection of the conjugate vaccine. These antibodies were able to neutralize the virus in vitro and provided partial protection from a challenge with a lethal dose of WNV. Three injections of the vaccine induced high titers of virus-neutralizing antibodies, and completely protected mice from WNV infection. Conclusions The immunogenicity of DIII can be strongly enhanced by conjugation to virus-like particles of the bacteriophage AP205. The superior immunogenicity of the conjugate vaccine with respect to other DIII-based subunit vaccines, its anticipated favourable safety profile and low production costs highlight its potential as an efficacious and cost-effective prophylaxis against WNV.